KEBIJAKAN PERPUSTAKAAN DAN GALERI DI KAWASSAN PUSPITEK SERPONG - ROCHANI NANI RAHAYU (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Motivated by the concept of galleries, libraries, archives, and museums,that begun to growth, research was conducted using descriptive methods, against three libraries in the Serpong Puspiptek Area, namely the Data and Scientific Documentation Center Library of the Indonesian Institute of Sciences (PDII-LIPI), the Library of the Center for The Utilization of Informatics and Nuclear Strategic Area (PPIKSN BATAN), and the Library of the Management Information Center (PIM -BPPT), and the Puspitek Gallery. Data collection is taken from the website of each library website, Puspiptek website and Puspiptek Gallery The policy in providing services provide by the three libraries is similar, namely services are prioritized for the internal community of each agency, but if there is a library from outside the institution is still served. Puspiptek Gallery contains information about all research laboratories located in the area, and is open to the public.